Comparison of self-efficacy regarding lower extremity orthotics in physical therapy students before and after the implementation of prosthetics and orthotics lecture - 宮原 拓也; 高島 恵 (Journal of Assistive Technology in Physical Therapy, 2022)
This study aimed to investigate the self-efficacy of second-year students from a physical therapy vocational school regarding lower extremity orthoses before and after the implementation of the prosthetics and orthotics. We included 38 second-year students from a three-year physical therapy vocational school and collected information on their age, sex, and self-efficacy regarding lower extremity orthosis prior to the implementation of prosthetics and orthotics. The prosthetics and orthotics implementation included a video presentation on the use and adjustment of lower extremity orthoses, followed by a practical lecture on the selection, use, and adjustment of lower extremity orthoses. We again assessed the self-efficacy of the students after the implementation of prosthetics and orthotics and investigated whether they watched the videos and practiced lower extremity orthosis. As a result, self-efficacy after the implementation of prosthetics and orthotics improved significantly in all items compared to before the implementation. However, the results of comparisons between items indicated that the “process of selecting the lower extremity orthosis” and “determining the ankle joint angle” were issues. Therefore, although prosthetics and orthotics were effective, differences between items became an issue.